Impurity migration and effects on vacancy formation enthalpy in polycrystalline depleted uranium - Lund, K. R. (2015)
We have used Doppler-broadening of the positron-electron annihilation radiation technique and VASP calculations to verify the previously reported vacancy formation enthalpy Hvf in polycrystalline depleted uranium. Experimentally we have confirmed a Hvf of (1.6 ± 0.2) eV. VASP calculations using GGA and LDA approximations gave vacancy formation enthalpies values of 1.98 eV and 2.22 eV respectively. We found residual oxygen in the sample diminished these values by 50% or more. Our new experimental and theoretical data supports the notion that oxygen impurities in the sample are responsible for lower values of vacancy formation enthalpies. Measured and calculated vacancy formation enthalpies, as well as the obtained oxygen migration enthalpy of (0.6 ± 0.1) eV, are compared and discussed with values reported in the literature.